Hydroponic Farming of Leafy Vegetables: A Soil-less Approach to Sustainable Cultivation - Kafle, Anjina; Chaudhary, Anup; Dhital, Shambhu Prasad; Pajiyar, Roshan; K.C., Ganesh (Nexus: Journal of Interdisciplinary Engineering, Technology and Management, 2026)
Background: Hydroponics, a soilless cultivation technique, has emerged as a sustainable alternative to traditional agriculture. With increasing urbanization, limited arable land, and climate variability, hydroponics offers efficient resource use and consistent crop production. Leafy vegetables are particularly responsive to hydroponic systems, making them ideal for evaluating productivity and nutritional outcomes. Purpose: The purpose of the present research was to assess the growth performance, yield, and adaptability of selected crops, mustard greens, radish greens, Swiss chard, strawberries, and long beans, cultivated in a hydroponic vertical pipe system. The study aimed to determine crop suitability, nutrient uptake patterns, and overall system productivity. Research Methodology: Four Horizontal pipes were established, each containing a different crop group. Pipe 1 contained mustard greens, Pipe 2 radish greens, Pipe 3 Swiss chard, and Pipe 4 a mixed system of strawberries and long beans. Growth parameters, including leaf expansion, stem strength, chlorophyll intensity, biomass accumulation, and flowering, were monitored. Observations were recorded systematically to evaluate crop performance under uniform nutrient solution and controlled environmental conditions. Results Mustard greens showed rapid vegetative growth and produced the highest biomass among leafy crops. Radish greens demonstrated moderate growth, with high chlorophyll intensity and adaptability. Swiss chard produced the largest leaf area and highest leaf quality, making it visually and nutritionally optimal. Strawberries established strong root systems and flowered early, while long beans displayed vigorous vine elongation and required support structures. Overall, the horizontal hydroponic system supported robust development across all crop groups. Conclusions: The study confirms that leafy vegetables such as mustard greens and Swiss chard are highly suitable for hydroponic vertical systems, while radish greens provide resilience under varying conditions. The successful establishment of strawberries and long beans highlights the versatility of hydroponics for mixed cropping strategies. Implication: These findings underscore hydroponics as a sustainable, resource-efficient farming method capable of addressing food security challenges. Future applications include scaling vertical systems for urban agriculture, integrating automation and Internet of Things technologies, and expanding crop diversity to enhance productivity and resilience in both urban and rural contexts.